Risk factors associated with early neonatal sepsis in preterm infants of the national Child mother teaching hospital, 2017 - Gretzelle Burga-Montoya; Consuelo Luna Muñoz; Lucy Correa López (Revista de la Facultad de Medicina Humana, 2019)
Introduction: Neonatal sepsis is one of the most important diseases of our country, it is necessary to know its risk factors in our country. Objetive: To determine the risk factors associated with early neonatal sepsis in preterm infants of the National Mother Teaching Hospital San Bartolomé in 2017. Methods: Case-control, observational, analytical, cross-sectional and retrospective study. will work with medical records. The dependent variable was early neonatal sepsis. We worked with a sample size of 62 cases and 124 controls (ratio 1: 2). The data was obtained from the medical records. For inferential statistics, bivariate analysis was used to find the Odds Ratio with their respective 95% confidence intervals. Values p <0,05 wereconsidered statistically significant. Results: Of the 186 patients studied, 53.8% were female. The factors associated with early neonatal sepsis were: low birth weight -ORa: 4,031 (95% CI: 1,743-9,318); age 35 to over -ORa: 2,729 (95% CI: 1,266-5,88); less than 6 prenatal controls -ORa: 3,315 (IC95%: 1,452-7,567); urinary tract infection (UTI) in the 3rd quarter -ORa: 2,947 (95% CI: 1,063-8,174); meconial fluid -ORa: 5,822 (95% CI: 1.92-17.653) and premature rupture of membranes -ORa: 2,789 (95% CI: 1,035- 7,511). Discussion: A significant association has been found between early neonatal sepsis and low birth weight, age 35 to more, fewer than 6 prenatal controls, UTI in the third trimester, meconium fluid and premature rupture of membranes.